Finite time blow-up for a semilinear generalized Tricomi system with mixed nonlinearity. (October 2022) - Fan, Mengting; Geng, Jinbo; Lai, Ning-An; Lin, Jiayun
Abstract: There is a large literature about blow-up and lifespan estimate for semilinear generalized Tricomi equation with power type nonlinear terms | u | p or | u t | p . In this work, we are devoted to studying the blow-up phenomenon for the coupled semilinear generalized Tricomi system including both of these two nonlinearities. To this end, asymptotic behavior of the solutions to two second order ordinary differential equations are investigated.